PERKEMBANGAN TAFSIR FALSAFI DALAM RANAH PEMIKIRAN ISLAM - Syafieh Syafieh (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2017)
This article will explain about the development of philosophical interpretation from classical to modern era. The emergence of the medieval philosophical interpretation has provided a new insight into the development of interpretation. The existence of this style of philosophical interpretation is also the